Molecular Engineering‐Based Aptamer–Drug Conjugates with Accurate Tunability of Drug Ratios for Drug Combination Targeted Cancer Therapy. (19th July 2019) - Zhou, Fang; Wang, Peng; Peng, Yongbo; Zhang, Pengge; Huang, Qin; Sun, Weidi; He, Nongyue; Fu, Ting; Zhao, Zilong; Fang, Xiaohong; Tan, Weihong
Abstract: Polytherapy (or drug combination cancer therapy (DCCT)), targeting multiple mechanisms associated with tumor proliferation, can efficiently maximize therapeutic efficacy, decrease drug dosage, and reduce drug resistance. However, most DCCT strategies cannot coordinate the specific delivery of a drug combination in an accurately tuned ratio into cancer cells. To address these limitations, the present work reports the engineering of circular bivalent aptamer–drug conjugates (cb‐ApDCs). The cb‐ApDCs exhibit high stability, specific recognition, excellent cellular uptake, and esterase‐triggered release. Furthermore, the drug ratios in cb‐ApDCs can be tuned for an enhanced synergistic effect without the need for complex chemistry. Therefore, cb‐ApDCs provide a promising platform for the development of DCCT strategies for different drug combinations and ratios. Abstract : Viele Vorteile : Zirkuläre bivalente Aptamer‐Wirkstoff‐Konjugate (cb‐ApDCs) für die Wirkstoffkombinationstherapie von Krebs (DCCT) wurden entwickelt. Sie bieten hohe Stabilität, spezifische Erkennung, exzellente Zellaufnahme, Esterase‐induzierte Freisetzung und abstimmbare Wirkstoffverhältnisse für einen erhöhten synergistischen Effekt.